Stable isotope tracing reveals compartmentalized nitrogen assimilation in scleractinian corals - Chiles, Eric N.; Huffmyer, Ariana S.; Drury, Crawford; Putnam, Hollie M.; Bhattacharya, Debashish; Su, Xiaoyang (Frontiers in Marine Science, 2022)
Corals form symbiotic relationships with dinoflagellate algae of the family Symbiodiniaceae, bacteria, and other microbes. Central to that relationship is the regulation of nutrition flux between the animal host and the photosynthetic Symbiodiniaceae that it is reliant on for the majority of metabolic needs. Nitrogen availability controls the growth and density of Symbiodiniaceae within coral tissues and has been proposed to play a role in host derived symbiosis regulation. Warming ocean temperatures and subsequent increases in dissolved organic carbon can potentially increase nitrogen fixation and lead to bleaching. We investigated the importance of nitrogen metabolism in vivo with LC-MS based stable isotope tracing using nubbins from three species of Hawaiian coral, the more heat tolerant Montipora capitata and Porites compressa and the more heat sensitive Pocillopora acuta, that were collected from reefs in Kāne’ohe Bay, O’ahu. In addition to 15N incorporation into nucleotides, amino acids, and urea cycle metabolites, we also observed significant isotopic labeling in dipeptides, supporting their previous identification as major heat stress response metabolites. Surprisingly, the dipeptides are highly enriched in 15N compared to free amino acids, which are the biosynthetic precursors for dipeptides. This suggests that there is a high turnover of dipeptide pools and distinct biosynthetic mechanisms that separately mediate amino acid and dipeptide production. These preliminary data show that nitrogen assimilation in the coral holobiont is likely compartmentalized, with rapid assimilation and quick dipeptide turnover occurring in one region of the holobiont and slow turnover of other nitrogen containing metabolites in other region(s).